Unlocking the Potential of Finger Millet in Child Nutrition: An Overview of Nutritional Power, Processing Methods and Policy Frameworks for Strategic Interventions. - BODA, NIKHITA RAMESH; KADRI, AFIYA SAYED; RAJENDRAN, ANANTHAN; BANJARA, SANTOSH KUMAR; GUPTA, SOURAV SEN; SHARMA, PARAS; RAI, SAKSHI; GEDDAM, JAG JEEVAN BABU; PARASANNANAVAR, DEVARAJ (Current Research in Nutrition & Food Science, 2025)
In the realm of nutritional science, Finger Millet (Ragi), rich in essential nutrients, stands out as a powerful ally against childhood malnutrition. Revered for its protein content (7-8g) with vital amino acids, minerals especially calcium (364-400mg), dietary fiber (11-12%), diverse array of phytonutrients contribute to overall well-being. Yet, amidst its nutritional splendor, harbors antinutrients notably tannins and phytates can hinder mineral absorption that can be reduced by a spectrum of processing techniques (soaking, boiling, sprouting, roasting, fermentation). In addition, Ragi enhances colonic microbial diversity. Ultimately, offering a diverse culinary application that blends tradition and modernity. This review navigates through its nutritional composition, strategies to mitigate Antinutrients, its positive impact on gut microbiome and malnutrition. Embarking on a journey that spans the interdisciplinary domains of agronomy, food science, and public health, this study underscores the imperative of integrating Finger Millet into dietary paradigms. Such integration aims not only to elevate nutritional outcomes but also to fortify the resilience of food ecosystems. By delving into the socio-economic and cultural details surrounding cultivation and consumption, this review advocates for concerted efforts to harness the nutritional potential of this Indigenous grain, tackling the urgent challenge of undernutrition while fostering robust food security systems.